An Audience of One : Dorothy Osborne's Letters to Sir William Temple, 1652-1654. - Hintz, Carrie (University of Toronto Press, 2014)
Combining historical and biographical research with feminist theory, Carrie Hintz considers Osborne's vision of letter writing, her literary achievement, and her literary influences.